2014
DOI: 10.1093/mnras/stu872
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of neutrino cooling in the SN1987A scenario

Abstract: The neutrino signal from SN1987A confirmed the core-collapse scenario and the possible formation of a neutron star. Although this compact object has eluded all observations, theoretical and numerical developments have allowed a glimpse of the fate of it. In particular, a hypercritical accretion model has been proposed to forecast the accretion of ∼ 0.15 M in two hours and the subsequent submergence of the magnetic field in the newborn neutron star. In this paper, we revisit the Chevalier's model in a numerical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Moreover, Chevalier (1989) estimated a total fallback around 0.1 M ⊙ for SN 1987A, which is supposed to be an unusually high value compared to "normal" type II supernovae. Recent multi-dimensional numerical simulations by Bernal et al (2013); Fraija et al (2014) confirmed this scenario and furthermore showed that such a hypercritical accretion can lead to a submergence of the magnetic field, giving a natural explanation why the neutron star (possibly) born in SN 1987A has not been found yet.…”
Section: Amount Of Fallbackmentioning
confidence: 89%
“…Moreover, Chevalier (1989) estimated a total fallback around 0.1 M ⊙ for SN 1987A, which is supposed to be an unusually high value compared to "normal" type II supernovae. Recent multi-dimensional numerical simulations by Bernal et al (2013); Fraija et al (2014) confirmed this scenario and furthermore showed that such a hypercritical accretion can lead to a submergence of the magnetic field, giving a natural explanation why the neutron star (possibly) born in SN 1987A has not been found yet.…”
Section: Amount Of Fallbackmentioning
confidence: 89%
“…This resonance depends on the effective potential and neutrino oscillation parameters. The equations that determine the neutrino evolution in matter for two and three flavors are related as follows [27,56].…”
Section: Iii12 Resonant Oscillationsmentioning
confidence: 99%
“…Under normal SN conditions, over 99% of the energy released leaves the star as neutrinos, without further interaction. For SN 1987A [13] the kinetic energy was around E kin ∼ 1 B and the total energy released (in neutrinos) was E T ∼ 300 B. Assuming somewhat larger efficiency (larger density and temperature, thus, larger neutrino cross section), and considering we have more mass in the compact object we estimate the kinetic energy to be a few times larger than in SN 1987A, i.e., E kin ∼ 5 B, which coincides with the observations for GRB 110709B.…”
Section: Act Ii: Bh Formationmentioning
confidence: 99%